Role of ultrasonography in the evaluation of children with acute abdomen in the emergency set-up - Aviral; Chana R; Ahmad Ibne (Wolters Kluwer Medknow Publications, 2005)
Background: Acute abdomen in children has been aptly described as Pandora′s box. Unlike computerized tomography (CT scan), ultrasonography (USG) has no radiation hazard and the present study analyses the diagnostic yield of the USG in acute abdomen in children. Materials and Methods: Between September 2001 to October 2003, 75 patients with acute abdomen underwent clinical examination, routine biochemical tests, erect X-ray abdomen, USG and CT scan. Laparotomy and histological examination established final diagnosis. Results: The accuracy of correct diagnosis was 60%, 66.6%, 64%, 98.7% with clinical examination alone, USG alone, clinical examination combined with conventional radiography, and clinical evaluation combined with conventional radiography and USG respectively. USG helped to prevent unnecessary laparotomy in 16.3% of patients. Conclusions: USG is good investigative modality in the management of acute abdomen in children.